Development of Discovery Learning-Based E-LKPD to Enhance Students' Learning Motivation and Achieve Critical Thinking Skills in Salt Hydrolysis Material - Hayyun; Ibnu haldun; Sri Winarni (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to evaluate the viability, practicality, and effectiveness of based on discovery learning (E-LKPD) in raising students' motivation to learn and cultivating their critical thinking abilities (CTS). This study adopts a quantitative methodology by utilizing the research and development (R&D) technique and the Borg and Gall model. Sixty-two students from SMA Negeri 1 Baitussalam's class XI make up the study sample. The average results of the viability test for the E-LKPD, reviewed from the aspects of material completeness, accuracy, currency, and alignment with objectives, obtained a percentage of 91.25% with the criterion of "very feasible." Meanwhile, the practicality of the E-LKPD based on the responses from students and teachers achieved average percentages of 87.38% and 82.5%, respectively, with the criterion of "very practical." The effectiveness assessment of the E-LKPD, based on non-test results of learning motivation with an N-Gain percentage of 0.56 and the students' CTS test results with a completeness percentage of 79.48, falls under the criterion of "quite effective." Therefore, it can be concluded that this discovery learning-based E-LKPD is viability, practicality, and effectiveness in enhancing learning motivation and achieving students' critical thinking skills (CTS).